Cosmological solutions for particular case of modified theory of gravity with a Brans-Dicke field. - Жубатканова, Ж; Мырзакулов, Н; Мейрбеков, Б (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this article was investigate a special case of F(R, T) gravity in the form of F(R) gravity in the Palatini formalism which is equivalent to the Brans-Dicke theory with the ω =-3/2 parameter in a locally symmetric type Bianchi I spacetime . The Lagrangian of this model is derived. The equations of motion for a model with a Brans-Dicke type scalar field are found. Using the proportionality between the expansion scalar and the shear scalar are found cosmological solutions for this model.